Characterization of retinal microvasculature and structure in atrial fibrillation - Liu, Junfeng; Tao, Wendan; Li, Dayan; Kwapong, William Robert; Cao, Le; Zhang, Xiaoling; Ye, Chen; Chen, Shi; Liu, Ming (Frontiers in Cardiovascular Medicine, 2023)
Background and objective Quantitative changes in retinal microvasculature are associated with subclinical cardiac alterations and clinical cardiovascular diseases (i.e., heart failure and coronary artery disease). Nonetheless, very little is known about the retinal vascular and structural changes in patients with atrial fibrillation (AF). Our study aims to characterize the microvasculature and structure of the retina in AF patients and explore their differences in different types of AF (paroxysmal and sustained AF). Methods This cross-sectional study was conducted at the Departments of Neurology and Cardiology in West China Hospital, Chengdu, China. Individuals aged 40 years or older with a diagnosis of AF were eligible for inclusion and underwent an evaluation and diagnosis confirmation before enrollment. Control individuals aged 40 years or older and without a history of AF, ocular abnormalities/disease, or any significant systemic illness were recruited. The retinal vascular and structural parameters were assessed using swept-source optical coherence tomography (SS-OCT)/SS-OCT angiography. Echocardiographic data of left atrium (LA) diameter were collected in patients with AF at the time of inclusion. Results A total of 242 eyes of 125 participants [71 men (56.8%); mean (SD) age, 61.98 (8.73) years] with AF and 219 eyes of 111 control participants [53 men (47.7%); mean (SD) age, 62.31 (6.47) years] were analyzed. In our AF cohort, 71 patients with paroxysmal AF and 54 patients with sustained AF (i.e., persistent/permanent AF) were included. Decreased retinal microvascular perfusion (β coefficient = −0.08; 95% CI, −0.14 to −0.03) and densities (β coefficient = −1.86; 95% CI, −3.11 to −0.60) in superficial vascular plexus (SVC) were found in the eyes of the participants with AF. In regard to retinal structures, thinner ganglion cell–inner plexiform layer (GCIPL; β coefficient = −2.34; 95% CI, −4.32 to −0.36) and retinal nerve fiber layer (RNFL) thicknesses (β coefficient = −0.63; 95% CI, −2.09 to −0.18) were observed in the eyes of the participants with AF. The retinal parameters did not significantly differ between paroxysmal and sustained AF (all P > 0.05). However, significant interactions were observed between LA diameter and AF subtypes with the perfusion and densities in SVC (P < 0.05). Conclusion This study found that individuals with AF had decreased retinal vascular densities and perfusion in SVC, as well as thinner GCIPL and RNFL thickness compared with age- and sex-matched control participants. The differences of the retinal microvasculature in SVC between paroxysmal and sustained AF depend on the LA diameter. Given our findings, further longitudinal studies with our participants are of interest to investigate the natural history of retinal microvascular and structural changes in individuals across the clinical process of AF and AF subtypes.